2021
DOI: 10.11158/saa.26.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of the genus Flagellozetes Balogh, 1970 (Acari: Oribatida: Galumnidae) from Vietnam

Abstract: Oribatid mite fauna of Vietnam is most studied among countries of Continental Southeast Asia but due to the brief history of detailed research, discoveries of new species are expected. Descriptions of two new species of oribatid mites (Oribatida) of the family Galumnidae—Flagellozetes (Cosmogalumna) sacculus sp. nov. and F. (C.) lineatus sp. nov.—are presented based on specimens collected from rainforest soil of Bi Dup—Nui Ba National Park (southern Vietnam). F. (C.) sacculus sp. nov. differs from other specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Regarding interspecific differences of morphological characters, it is evident that there is significant ornamentation and pore area varies widely among species within the subgenus, especially the ornamentation on the notogaster. Kolesnikov and Leonov (2021) suggested that the evolution of sacculonotic species within mainly poronotic genera and families is possible and considered as independent of the mode of reproduction, and think that all other characters for F. (Cosmogalumna) sacculus are markedly characteristic, in addition, proposed the description of the new subgenus of Flagellozetes in the future based on new data for this species (using the morphology of ontogenetic instars and DNA sequence data) or the discovery of a complex of morphologically similar species. Subsequently, Subias (2023) included F. (C.) sacculus in Aliuscosmogalumna.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding interspecific differences of morphological characters, it is evident that there is significant ornamentation and pore area varies widely among species within the subgenus, especially the ornamentation on the notogaster. Kolesnikov and Leonov (2021) suggested that the evolution of sacculonotic species within mainly poronotic genera and families is possible and considered as independent of the mode of reproduction, and think that all other characters for F. (Cosmogalumna) sacculus are markedly characteristic, in addition, proposed the description of the new subgenus of Flagellozetes in the future based on new data for this species (using the morphology of ontogenetic instars and DNA sequence data) or the discovery of a complex of morphologically similar species. Subsequently, Subias (2023) included F. (C.) sacculus in Aliuscosmogalumna.…”
Section: Discussionmentioning
confidence: 99%